(untitled) (MATEMATIKA, 2025)
The increase in reliance on online meal delivery services and take-outs due to changes in consumer behavior has resulted in an escalation in the consumption and disposal of single-use plastics. With the mounting apprehension over the ecological consequences of the increased plastic waste, finding effective solutions is a crucial concern. This study aims to determine the priority of criterion for reducing plastic waste in the foodservice sector using the Fuzzy Analytic Hierarchy Process (FAHP) method. An onsite survey via questionnaire was conducted to gather responses from 16 key players who were involved directly and indirectly in plastic waste mitigation initiatives. The findings revealed that the key players prioritize the criteria related to harmonizing environmental impact, whereas public acceptance was assessed as being of lower priority. This article offers practical insights into single-use plastics in foodservice, using real data and perspectives from experts in the field to build on existing research.